Histopathological Study of Ovarian Cysts in Derna - Noria Raffalla; Amal Srgewa; Ibtesam Emnia (AlQalam Journal of Medical and Applied Sciences, 2024)
Ovarian cysts, which are sacs filled with fluid located in the ovaries, represent the primary reason for enlarged ovaries, impacting approximately 20% of women who experience a pelvic mass at least once during their lifetime. The present work was carried out to focus on the frequency, gross appearance and histopathological features of each type of ovarian cysts in Derna-City East of Libya. This work included 54 cases of ovarian cysts, out of 338 samples submitted to Noor-AL-Huda Medical Center Pathology Laboratory in Derna City –East of Libya during the period between January 2022 and April 2023, samples were formalin fixed, processed, then H &E sections were obtained for histologic diagnosis and subtyping. The age of patients ranges from 5 – 68 years, the predominant age group was 30– 39 years, 26 (48.14%) were on the right side, 23(42.59%) were on the left side, 5(9.25%) were bilateral. The commonest presenting symptoms were both incidental in 21(38.8%) and pain in 18(33.33%); the cyst mainly obtained from Cystectomy operation 39 (72.22%). Gross appearance of each type was studied. Out of the included 54 ovarian cysts 29 (53.70%) were non –neoplastic and25 (46.29%) were neoplastic. Follicle cysts represented (37.93%) of the non-neoplastic lesions, while serous cyst adenoma represented (40%) of the neoplastic lesions. We concluded that non-neoplastic cysts are the most common types of ovarian cysts. Among non-neoplastic ovarian cysts, the functional cysts including follicular and corpus luteal cysts were the most common, while serous cysts and teratomas are the common neoplastic cysts. Most ovarian cysts are found on the right side. Histopathological examination is essential for accurate diagnosis and proper management of ovarian cysts. تمثل أكياس المبيض، وهي أكياس مملوءة بالسوائل الموجودة في المبيضين، السبب الرئيسي لتضخم المبايض، حيث تؤثر على ما يقرب من 20٪ من النساء اللاتي يعانين من كتلة في الحوض مرة واحدة على الأقل خلال حياتهن. تم تنفيذ العمل الحالي للتركيز على التكرار والمظهر الإجمالي والسمات النسيجية المرضية لكل نوع من أكياس المبيض في مدينة درنة شرق ليبيا. شمل هذا العمل 54 حالة لتكيسات المبيض، من أصل 338 عينة مقدمة إلى مختبر علم الأمراض بمركز نور الهدى الطبي بمدينة درنة – شرق ليبيا خلال الفترة ما بين يناير 2022 وأبريل 2023، وتم تثبيت العينات بالفورمالين ومعالجتها ثم ح تم الحصول على أقسام & E للتشخيص النسيجي والتصنيف الفرعي. تتراوح أعمار المرضى بين 5 - 68 سنة، وكانت الفئة العمرية السائدة 30 - 39 سنة، 26 (48.14٪) كانوا على الجانب الأيمن، 23 (42.59٪) كانوا على الجانب الأيسر، 5 (9.25٪) كانوا ثنائيين . كانت الأعراض الأكثر شيوعًا عرضية في 21 (38.8٪) والألم في 18 (33.33٪)؛ الكيس الذي تم الحصول عليه بشكل رئيسي من عملية استئصال المثانة 39 (72.22%). تمت دراسة المظهر الإجمالي لكل نوع. من بين 54 كيسة مبيضية، 29 (53.70%) كانت غير ورمية و25 (46.29%) كانت ورمية. تمثل الأكياس الجريبية (37.93%) من الآفات غير الورمية، بينما يمثل الورم الحميد الكيسي المصلي (40%) من الآفات الورمية. وخلصنا إلى أن الأكياس غير الورمية هي أكثر أنواع أكياس المبيض شيوعا. من بين أكياس المبيض غير الورمية، كانت الأكياس الوظيفية بما في ذلك أكياس المبيض الجريبي وأكياس الجسم الأصفر هي الأكثر شيوعًا، في حين أن الأكياس المصلية والأورام المسخية هي الأكياس الورمية الشائعة. تم العثور على معظم أكياس المبيض على الجانب الأيمن. الفحص النسيجي ضروري للتشخيص الدقيق والإدارة السليمة لكيسات المبيض